Challenging the journalistic ideal of objectivity in reporting vaccination - Wan Mohd Ghazali, Wan Norshira; Mohamed, Shafizan; Yusoh, Mohd Helmi (Kulliyyah of Medicine, IIUM, 2022)
INTRODUCTION:The resurgence of vaccine-preventable diseases such as polio, diphtheria, measles, mumps, among others demonstrate the anti-vaccine movement's growing popularity and efficacy in spreading its views. To overcome the vaccine fallacies that are now prevalent, effective news media coverage on vaccination that emphasises the urgency and necessity of vaccination to the public is required. To determine whether such emphasis is made in the mainstream media, this study analysed vaccine coverage in two English newspapers in Malaysia, The Star and the New Straits Times (NST). MATERIALS AND METHODS:Framing analysis was performed on a total of 308 vaccine-related news items gathered over 14 months, from January 2019 to March 2020. RESULTS: Both publications used almost similar patterns in reporting vaccine-related issues. They relied heavily on official or government institutions as sources of information with high emphasis given on creating awareness and providing information about vaccines. In broad, vaccination is primarily covered as news to be reported, rather than a problem to be highlighted and further explored in-depth. CONCLUSION: Considering contemporary health realities, newspapers must play a persuasive and consistent role in publicising the necessity of immunisation.